Éducation physique et culture sportive au Brésil à l’époque contemporaine : entre utilité sociale et reconnaissance identitaire - Jean-Pierre Blay (Cahiers des Amériques Latines)
Physical Education (PE) came out very early in the Brazilian education system, both in teacher training and in the program of elementary and high school. Educational content and circulation of knowledge which defined the basis of this course, were built up around the gym until the end of the “Estado Novo”. In this scenario, the role and interest of the state varied according to political regimes. Between the two world wars, PE was sometimes marginalized because it was not considered as a school subject and sometimes suffered impact of hygienists theories and natural method (French). In the sixties, PE changed with the action of teachers who have found in the French human sciences the means of expression of a claim of identity. The return to democracy in the eighties, coincided with the capture of the history of PE by their own teachers whose goal was democratizing the sport. Only when PE incorporated auxiliary sciences and was enriched with the sports culture, it obtained its recognition of identity. We see in this evolution, the emergence of new sports disconnected from school system and the projection of a history of sport in Brazil coming up from a cultural history of urban societies.